2018
DOI: 10.5826/dpc.0801a05
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on the nail plate for treatment of ingrown toenail

Abstract: BackgroundOur routine treatment for ingrown toenail was removal of the surrounding soft tissue and shortening the bone of the distal phalanx. We determined the range and volume of excision based on our experience without an objective standard and routinely performed avulsion of the nail plate.ObjectiveTo take the nail plate as an objective mark during surgical treatment of ingrown toenail to ensure accurate excision.Patients and MethodsFifteen patients with ingrown toenails were treated with this technique. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Complications following surgical interventions may include significant postoperative pain, prolonged wound healing, risk of bone infection or other infections, and a longer recovery period compared to conservative methods. 2,13 In order to avoid surgical treatment requiring convalescence, alternative methods should be considered if the nail condition is not a contraindication. One of the few methods to correct ingrown nails is the three-part VHO-Osthold® Perfect orthonic buckle, which is the domain of podiatrists and professionals in foot care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Complications following surgical interventions may include significant postoperative pain, prolonged wound healing, risk of bone infection or other infections, and a longer recovery period compared to conservative methods. 2,13 In order to avoid surgical treatment requiring convalescence, alternative methods should be considered if the nail condition is not a contraindication. One of the few methods to correct ingrown nails is the three-part VHO-Osthold® Perfect orthonic buckle, which is the domain of podiatrists and professionals in foot care.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical treatment can achieve a rapid effect by completely removing the completely ingrown nail or the surrounding tissue, it should be borne in mind that these are invasive actions and can lead to deformations of the nail plate at a later stage of its growth. Complications following surgical interventions may include significant postoperative pain, prolonged wound healing, risk of bone infection or other infections, and a longer recovery period compared to conservative methods 2,13 . In order to avoid surgical treatment requiring convalescence, alternative methods should be considered if the nail condition is not a contraindication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment can be approached either conservatively (non-surgical) or surgically. Conservative treatment is often effective for stage I, whereas stages II and III often require surgical intervention [22,23]. A 2012 Cochrane systematic review concluded that surgical interventions were more effective in preventing recurrence, especially when coupled with phenol application, but more evidence-based research was required [2].…”
Section: Treatmentmentioning
confidence: 99%